2003
DOI: 10.1351/pac200375050631
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruptors in the environment (IUPAC Technical Report)

Abstract: Republication or reproduction of this report or its storage and/or dissemination by electronic means is permitted without the need for formal IUPAC permission on condition that an acknowledgment Endocrine disruptors in the environment (IUPAC Technical Report)Abstract: Many chemical substances of natural or anthropogenic origin are suspected or known to be endocrine disruptors, which can influence the endocrine system of life. This observation has led to increased interest on the part of the public and the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0
82

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(209 citation statements)
references
References 145 publications
2
122
0
82
Order By: Relevance
“…phenolic compounds such as nonylphenol and bisphenol A [5] (NRP50 project PHENCON), flame retardants (projects FLARE and ENDAIR [6] ) and UV filters [7] (project HAUS). Beside household and industrial sources, also agriculture contributes to the pool of endocrine disrupting chemicals, including steroidal estrogens [8] but also phytoestrogens and estrogenic mycotoxins have been considered. [9] Although various studies indicate that the steroidal estrogens are the main causative agents of the estrogenic activity of effluent and receiving waters, there is a risk associated with a targeted analysis for just a limited number of known estrogenic substances.…”
Section: Introductionmentioning
confidence: 99%
“…phenolic compounds such as nonylphenol and bisphenol A [5] (NRP50 project PHENCON), flame retardants (projects FLARE and ENDAIR [6] ) and UV filters [7] (project HAUS). Beside household and industrial sources, also agriculture contributes to the pool of endocrine disrupting chemicals, including steroidal estrogens [8] but also phytoestrogens and estrogenic mycotoxins have been considered. [9] Although various studies indicate that the steroidal estrogens are the main causative agents of the estrogenic activity of effluent and receiving waters, there is a risk associated with a targeted analysis for just a limited number of known estrogenic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Embora já existissem, desde o início do século XX, hipóteses prevendo alterações no funcionamento do sistema endócrino de algumas espécies animais expostas a determinadas substâncias quí-micas tóxicas, apenas recentemente esta importante questão tem recebido atenção por parte da comunidade científica, principalmente devido ao número crescente de publicações que relatam o aumento da incidência de disfunções no sistema endócrino de seres humanos (incluindo a infertilidade masculina) e, mais significativamente, efeitos fisiológicos adversos observados em espécies animais para as quais a relação causa/efeito é mais evidente. De fato, as evidências observadas em estudos envolvendo moluscos, crustáce-os, peixes, répteis, pássaros e alguns mamíferos têm sugerido que possíveis alterações de saúde humana envolvendo o sistema reprodutivo, tais como o câncer de mama e de testículo, podem estar relacionadas à exposição a tais substâncias [3][4][5][6][7][8] .Uma grande parte da evidência dos possíveis efeitos destas substâncias em seres humanos foi obtida a partir da experiência envolvendo mulheres grávidas que tomaram o estrogênio sintético dietilestilbestrol (DES), prescrito para evitar o aborto espontâneo e promover o crescimento do feto, no período entre 1948 a 1971. Muitas das filhas dessas mulheres são hoje estéreis e, uma minoria, tem desenvolvido um tipo raro de câncer vaginal.…”
unclassified
“…During the last 20 years, an enormous public and scientific interest was focused on these substances, resulting in many publications on generation, input, and behavior in the environment (Giacomini et al, 2006;Lintelmann et al, 2003;US EPA, 1994). These toxicants have a potent concern for public health: several in vitro and in vivo experiments have suggested that PCDDs and PCDFs may interfere with thyroid function (Boas et al, 2006;Giacomini et al, 2006).…”
Section: Dioxins and Furansmentioning
confidence: 99%
“…www.intechopen.com The high persistence of PCBs in adipose tissues and their toxic potential for animals and humans (Breivik et al, 2002;Fisher, 1999), resulted in an almost international production stop in the 1970-80s (Lintelmann et al, 2003). However, the PCB properties, such as chemical and thermal stability, noninflammability, high boiling points, high viscosity, and low vapor pressure, are the reason for their worldwide distribution (Safe, 2000).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
See 1 more Smart Citation